2013
DOI: 10.1155/2013/604860
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Hepatocellular Adenoma in the United States: Review of the Literature

Abstract: Hepatocellular adenoma (HCA) is a benign neoplasm arising from hepatocytes. There is evidence that the inflammatory subtype may be associated with obesity and alcohol use and that men with metabolic syndrome may be at risk for malignant transformation of HCA. We sought to explore the combined experience of US centers as reported in the literature to document the epidemiologic shift in risk factors for HCA formation in the United States, namely, a shift from oral contraceptive pills (OCPs) to an emerging role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 37 publications
(47 reference statements)
3
56
1
Order By: Relevance
“…Newer generation contraceptive pills with lower estrogen content are likely associated with a lower risk of hepatic adenomas. Despite that, the overall incidence of hepatic adenomas has not decreased 58 . This can perhaps be explained by the increasing rates of obesity worldwide and an associated increase in metabolic syndrome, with a subset of those patients being diagnosed with hepatic adenomas, particularly the inflammatory and telangiectatic variant 55, 59 .…”
Section: Clinical and Radiologic Features Of The Common Liver Mass Lementioning
confidence: 99%
“…Newer generation contraceptive pills with lower estrogen content are likely associated with a lower risk of hepatic adenomas. Despite that, the overall incidence of hepatic adenomas has not decreased 58 . This can perhaps be explained by the increasing rates of obesity worldwide and an associated increase in metabolic syndrome, with a subset of those patients being diagnosed with hepatic adenomas, particularly the inflammatory and telangiectatic variant 55, 59 .…”
Section: Clinical and Radiologic Features Of The Common Liver Mass Lementioning
confidence: 99%
“…Discoveries of benign hepatocellular nodules including hepatocellular adenoma (HCA) and focal nodular hyperplasia (FNH) have increased due to the widespread use of imaging modalities as well as the recent increase in obesity in people . HCA are rare benign hepatocellular tumors reported to occur frequently in women taking oral contraceptives . In addition, glycogen storage disease and a specific form of diabetes (maturity‐onset diabetes of the young type 3, MODY3) are also indicated in its etiology .…”
Section: Introductionmentioning
confidence: 99%
“…Given the high number of patients with non cirrhotic NAFLD, screening for HCC in this population is not practicable [15] . Interestingly, the features of NAFLD-related HCC are similar to those of HCC of obese patients and of non-cirrhotic HCC, independently of the etiology [92,93] . Accordingly, it has been reported that obese patients have a relative risk of liver cancer of 189% relative to the 117% of overweight subjects [94] .…”
Section: Hcc In Nafld Chronic Hepatitismentioning
confidence: 84%